Da identidade goesa na diáspora - Fitas, Ana Paula (Trabalhos de Antropologia e Etnologia, 2020)
The assessment of the issue (s) of identity (s) of migrant population coming from the Indian territory, should, namely in the Goan case, take into account, specific data relating to their society of origin and the host society, so as not to conceal the importance of the starting and arrival time contexts. In analytical terms, it must, for epistemological reasons, consider that the facts and conditions identified in terms of starting perspective will determine the outcame of the final analysis.